2018
DOI: 10.1186/s12862-018-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytonuclear diversity and shared mitochondrial haplotypes among Daphnia galeata populations separated by seven thousand kilometres

Abstract: BackgroundThe zooplanktonic cladocerans Daphnia, present in a wide range of water bodies, are an important component of freshwater ecosystems. In contrast to their high dispersal capacity through diapausing eggs carried by waterfowl, Daphnia often exhibit strong population genetic differentiation. Here, to test for common patterns in the population genetic structure of a widespread Holarctic species, D. galeata, we genotyped two sets of populations collected from geographically distant areas: across 13 lakes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Similar evidence of rapid expansion has also been observed in other Daphnia species in Asia, such as D. mitsukuri Ishikawa, 1896 (Ma et al, 2019b) and D. galeata Sars, 1864 (Ma et al, 2015). In agreement with previous observations in other Daphnia species, for example, D. galeata (Thielsch et al, 2009;Yin et al, 2018) and D. mitsukuri (Ma et al, 2019b), we found that D. magna populations, regardless of their origin, had high relative clonal richness values (average R = 0.93), suggesting frequent sexual reproduction. However, high genetic diversity is not always a rule in Daphnia, as different species have different demographic histories (e.g., Zuykova et al, 2018a).…”
Section: Discussionsupporting
confidence: 89%
“…Similar evidence of rapid expansion has also been observed in other Daphnia species in Asia, such as D. mitsukuri Ishikawa, 1896 (Ma et al, 2019b) and D. galeata Sars, 1864 (Ma et al, 2015). In agreement with previous observations in other Daphnia species, for example, D. galeata (Thielsch et al, 2009;Yin et al, 2018) and D. mitsukuri (Ma et al, 2019b), we found that D. magna populations, regardless of their origin, had high relative clonal richness values (average R = 0.93), suggesting frequent sexual reproduction. However, high genetic diversity is not always a rule in Daphnia, as different species have different demographic histories (e.g., Zuykova et al, 2018a).…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with missing data at more than five microsatellite loci were excluded, resulting in a final data set of 1,777 individuals (there was no amplification bias among parental species and hybrids, data not shown). Of 44 analysed populations, mitochondrial data for 22 populations and microsatellite data for 13 populations have been published elsewhere (Ma et al, ; Wei et al, ; Yin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, D. sinensis populations, regardless of their origin, showed high relative clonal richness values (assessed by 12 microsatellites), suggesting frequent sexual reproduction. High clonal richness has also been observed in other Daphnia species, for example, D. galeata (Thielsch et al ; Yin et al ) and D. mitsukuri (Ma et al ). We detected very low clonal variation in D. sinensis in four Tibetan waterbodies (KLP, LZP, LZ3P, and SZP).…”
Section: Discussionmentioning
confidence: 85%
“…The genus Daphnia includes three subgenera: Daphnia, Hyalodaphnia, and Ctenodaphnia (Benzie 2005). Extensive biogeographical/population genetic studies have been carried out on members of the first two of these, including the Daphnia pulex species complex (e.g., Mergeay et al 2008;Vergilino et al 2011;Ma et al 2019b) and the Daphnia longispina species complex (e.g., Keller et al 2008;Petrusek et al 2008;Yin et al 2010Yin et al , 2018Ishida et al 2011;Ventura et al 2014). However, the last subgenus, Ctenodaphnia, has been the subject of very few taxonomy/biogeography studies (Adamowicz et al 2009;Petrusek et al 2013;Popova 2014).…”
mentioning
confidence: 99%